2023
DOI: 10.1371/journal.pone.0283928
|View full text |Cite
|
Sign up to set email alerts
|

Protective mucosal and systemic immunity induced by virus-like particles expressing Toxoplasma gondii cyst wall protein

Abstract: Toxoplasma gondii host cellular invasion factors such as the rhoptry proteins, micronemal antigens, or other subcellular compartment proteins have shown limited vaccine efficacies. T. gondii cyst wall protein (CST1) as a cyst persistence factor is critical for cyst wall integrity and bradyzoite persistence. Here, we generated influenza virus-like particles (VLPs) expressing the T. gondii CST1 and evaluated the mucosal as well as systemic immunities induced by VLPs. Intranasal immunization with the VLPs induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It has been reported that the nasal virus-like particle (VLP) vaccine, an alternative nanoparticle-based vaccine modality, triggered effective CSR to IgG/A to not only virus, 40 , 41 but also bacteria 42 or protozoa. 43 Given that the morphology of CPS14 + MVs resembles that of native viral virion (approximately 100 nm in diameter), the MV-based vaccine might induce potent immune responses through a nanopaticle-dependent manner similar to that of the VLP vaccine displaying antigens. 40 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the nasal virus-like particle (VLP) vaccine, an alternative nanoparticle-based vaccine modality, triggered effective CSR to IgG/A to not only virus, 40 , 41 but also bacteria 42 or protozoa. 43 Given that the morphology of CPS14 + MVs resembles that of native viral virion (approximately 100 nm in diameter), the MV-based vaccine might induce potent immune responses through a nanopaticle-dependent manner similar to that of the VLP vaccine displaying antigens. 40 …”
Section: Discussionmentioning
confidence: 99%